The socio-economic burden of snakebite in Sri Lanka - Kasturiratne, Anuradhani; Pathmeswaran, Arunasalam; Wickremasinghe, A. Rajitha; Jayamanne, Shaluka F.; Dawson, Andrew; Isbister, Geoff K.; de Silva, Hithanadura Janaka; Lalloo, David G. (PLOS Neglected Tropical Diseases, 2017)
Author summary Snakebite predominantly affects poor people in the rural tropics. The effect that snakebite has on these populations, both economically and in terms of death and disability, is poorly understood. We used data from a national household survey of snakebite in Sri Lanka to estimate the burden of death and disability and to calculate the financial cost of a snakebite episode for the Sri Lankan health system and for Sri Lankan households. We found that the burden of snakebite was considerable, similar to that of common diseases like meningitis or dengue and that treating snakebite cost the Sri Lankan government over $10 million each year. Despite health care being free in Sri Lanka, almost 80% of households experienced additional costs and loss of income following a snakebite; such costs are disastrous for poor rural workers.